Analysis of Security Issues for the Internet of Vehicles in India - Nithyanantham, S; S.Kannimuthu, Dr (International Journal of Engineering and Technology, 2017)
Internet of Vehicles is a popular one in this decade which plays a vital role in automobile industry. Where most of the vehicles used for public and private are integrated with various sensors and transistors which will be core essential for an intelligent vehicle a steady growth. In vehicles, the quantity of chips will also increase according to the development. The increase in the amount of data formed by these sensors appears to be more dramatic as sensors frequently produce data. It is important to store these data for future reference, analysis and finding valuable information like fault diagnosis information, GPS tracing, auto drive support etc. Inappropriately, the variety of data and volume becomes rapidly extreme. In large scales, the existing analytical techniques fail to work effectively and produces a lot of false positives, which under means their efficacy, when enterprises move to cloud architectures and gather massive data, the issues become more serious